x2-5x=-6

Move 6 to the left side of the equation by adding it to both sides.

x2-5x+6=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is 6 and whose sum is -5.

-3,-2

Write the factored form using these integers.

(x-3)(x-2)=0

(x-3)(x-2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-3=0

x-2=0

Set the first factor equal to 0.

x-3=0

Add 3 to both sides of the equation.

x=3

x=3

Set the next factor equal to 0.

x-2=0

Add 2 to both sides of the equation.

x=2

x=2

The final solution is all the values that make (x-3)(x-2)=0 true.

x=3,2

Solve Using the Square Root Property x^2-5x=-6